The role of lubricant feeding conditions on the performance improvement and friction reduction of journal bearings - Brito, F. P. (2013)
The performance of hydrodynamic journal bearings is significantly affected by the conditions under which the lubricant is fed to the bearing. However, many conventional analyses are not prepared to suitably incorporate these parameters and their effect on bearing performance, due to the over-simplified way they treat them. A thermohydrodynamic analysis suitable for conveniently deal with lubricant feeding conditions is now presented. It couples the numerical solution of the generalized Reynolds equation, the energy equations within the lubricant film and the heat transfer within the bush body. Special attention has been given to the treatment of the phenomena taking place within the grooves and in their vicinity, as well as to the ruptured film region. The effect that lubricant feed pressure and temperature, groove length ratio, groove width ratio and groove number (single / twin) have on bearing performance has been analyzed for a broad range of conditions. The results were found to be in good agreement with experimental published results and the robustness of the model to suitably treat these phenomena has been confirmed. It was found that a careful tuning of the feeding conditions may indeed improve bearing performance.